Vegetarian Dietary Patterns and Cognitive Function among Older Adults: The Adventist Health Study-2. Issue 4 (2nd October 2021) - Gatto, Nicole M.; Garcia-Cano, Jennifer; Irani, Crissy; Jaceldo-Siegl, Karen; Liu, Tiantian; Chen, Zhong; Paul, Jennifer; Fraser, Gary; Wang, Charles; Lee, Grace J.
Abstract: We explored effects on cognitive function of following plant-based vegetarian compared with non-vegetarian dietary patterns in otherwise healthy older community-dwelling members of the Adventist Health Study-2 cohort ( n = 132). Cognition was assessed using a comprehensive neuropsychological battery; a principal components analysis derived processing speed, executive function, and memory/language factors. Mild memory impairment (MMI) ( n = 26, 19.7%) was identified by memory tests. Vegetarians consumed (a) meats, fish, and dairy <1 time/month, (b) dairy ≥1 time/month and meats, and fish <1 time/month, or (c) fish ≥1 time/month, no limits on dairy, and meats <1 time/month. Dietary patterns were determined at baseline, for each decade, and at cognitive assessment; a diet stability score was calculated. Factor scores were not different between vegetarians and non-vegetarians, nor was dietary pattern associated with a lower odds of MMI. A more stable diet over the life course was associated with better memory/language [ β = 0.021 SE( β ) = 0.008; p = 0.01]. This exploratory study did not support differences in processing speed, executive function, or memory/language abilities between vegetarians and non-vegetarians but did suggest that a more stable dietary pattern which was characteristic of vegetarians was associated with better memory/language abilities.